2008
DOI: 10.1088/0957-4484/19/44/445717
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution and large dynamic range nanomechanical mapping in tapping-mode atomic force microscopy

Abstract: High spatial resolution imaging of material properties is an important task for the continued development of nanomaterials and studies of biological systems. Time-varying interaction forces between the vibrating tip and the sample in a tapping-mode atomic force microscope contain detailed information about the elastic, adhesive, and dissipative response of the sample. We report real-time measurement and analysis of the time-varying tip-sample interaction forces with recently introduced torsional harmonic canti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
120
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(126 citation statements)
references
References 49 publications
4
120
0
Order By: Relevance
“…In [44] polystyrene (E 2 ¼4 GPa) and highly oriented pyrolytic graphite (E 2 ¼5 Gpa) [44], their a 4 's are 18.7 and 23.4, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In [44] polystyrene (E 2 ¼4 GPa) and highly oriented pyrolytic graphite (E 2 ¼5 Gpa) [44], their a 4 's are 18.7 and 23.4, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Simultaneously to topography, phase (scale ¼ 30 deg), adhesion, peak force, dissipation, and elastic modulus (scale ¼ 5 GPa) were recorded (Berquand et al, 2009). based technique which allows one to perform the quantitative characterization of mechanical parameters of soft samples (mainly, elastic modulus, tip-sample adhesion force and tip-sample dissipation) with nanometrical lateral resolution (Sahin & Erina, 2008;Sahin, Magonov, Su, Quate, & Solgaard, 2007). Also, thermal characterization at the nanoscale has been performed on caramel using SThM (Morton et al, 2003).…”
Section: Scanning Probe Microscopy Based Techniques For Nanoscale Chamentioning
confidence: 99%
“…As in most cases the tip-sample interactions can be described with the DMT (Derjagin, Muller, Toropov) model [11,12], it can be easily shown that the dynamics of the tapping of the tip against the surface is related to the stiffness of the sample (Fig. 1).…”
Section: Principles Of the Torsional Bendigs Of The Cantilevermentioning
confidence: 99%
“…2). Although originally such cantilevers were used in much more complex [12][13][14], the mapping of surface's stiffness by utilizing the higher harmonic of the cantilever's torsional oscillation was successfully performed by Sahin [6]. It allowed observation of the changes of the PS and PMMA polymer film changes while the temperature increased.…”
Section: Principles Of the Torsional Bendigs Of The Cantilevermentioning
confidence: 99%